Feasibility of lung cancer RNA acquisition from a single transbronchial or transthoracic needle pass (FASTT trial). (January 2019) - Dotson, Travis; Bellinger, Christina; Su, Jing; Hansen, Kris; Parks, Graham E.; Cappellari, James O.; Craddock, Lou; Clark, Hollins; Howard, Clifford; Petty, W. Jeffrey; Prakash, Bharat; Watabe, Kounosuke; et al.
Highlights: Small volume biopsy samples in Non-Small Cell Lung Cancer face the challenge of supplying sufficient material. RNA extraction from a single needle aspirate provides enough material for tumor profiling. The FNA-based RNA quantification is consistent with RNA-Seq assays on bulk tissues. Translational implementation of biomarkers discovered from a single FNA pass is feasible. Abstract: Introduction: RNA isolation from tumor tissue is used for biomarker analyses and validation. Limited diagnostic material from small volume biopsies combined with an increasing demand for standard histologic, molecular characterization, and next generation sequencing applications often leads to limited material for research. We sought to evaluate small volume sampling of lung cancer tissue collected from a single needle pass during a diagnostic procedure and determine if it can provide RNA of acceptable quantity and quality. Methods: We enrolled 140 patients with probable primary bronchogenic carcinoma and collected RNA from a dedicated FNA aspiration. Total RNA (ηg), RNA integrity number (RIN), and %Mass in base pairs were evaluated from each patient sample. A customized nanoString nCounter® 95-gene panel was used to profile the expression patterns of feature NSCLC genes. We compared gene expression patterns that distinguish lung adenocarcinoma (LUAD) and squamous cell carcinoma (LUSC) in our cohort with a corresponding Cancer Genome Atlas (TCGA) NSCLC datasets. Results: Of the 149 patients consented. RNA-extraction was performed in 101 eligible patients. A satisfactory total RNA mass and RIN was quantified for all samples with a similar distribution among cellular subtypes. Mean %-Mass over 300 base pairs was noted for all specimens and 96% of samples met criteria to perform genetic evaluation with our commercialized gene expression assay. The FNA-derived transcriptomic results showed excellent consistency with the TCGA counterparts, and the differential expression pattern of LUAD vs LUSC subtypes were highly similar. Discussion: In this study, RNA retrieval from a single-pass FNA regardless of procedural approach showed equivalence and suitability for gene expression assessments. RNA extraction from small volume samples has the potential to provide valuable material for genetic profiling.